The tree diversity of Srengseng Urban Forest in DKI Jakarta - Layla Azizah Ditha Sari; Denni Susanto; Mukhlison (Foresty Faculty of Hasanuddin University, 2022)
Urban forests are part of urban green open spaces that are sought to be able to create a micro-climate and as a means of conservation for plants and the environment. The presence of urban forests is expected to be able to maintain urban ecosystems, so the presence of constituent trees becomes very important. This study aims to determine the tree species diversity of the Srengseng Urban Forest in DKI Jakarta. Data were collected using the systematic sampling method with nested sampling plots with 10% of sampling intensity. The results showed that the highest important value index at the seedling level was Adenanthera pavonina. Sapling and pole levels were dominated by Swietenia macrophylla. Meanwhile, the tree level was dominated by Gmelina arborea. The diversity index (H') of the urban forest at the seedling, sapling, pole, and tree were 1.32, 2.35, 2.24, and 2.81, respectively. Based on H’ value, the diversity index is in the low to moderate category. The research results will be useful for provincial governments as the basis for efforts to manage and develop the Srengseng Urban Forest.